Das Bild der Schweiz bei den Papstgesandten (1586-1654) : Die Ständige Nuntiatur in Luzern. Mit einer Dokumentation von Instruktionen und Berichten aus dem Geheimarchiv des Vatikans - Galgano, Mario (2021)
There was a special relationship between the papacy and the Swiss Confederacy in the early modern period. The "Romans" were not confronted with the usual monarchic-aristocratic structures. Taking a nuncio’s outside view provides revealing information. Galgano analyzes how the nuncios viewed Switzerland from 1586 to 1564 and provides future researchers with a valuable edition of their correspondence.